2015
DOI: 10.3899/jrheum.141129
|View full text |Cite
|
Sign up to set email alerts
|

Yoga in Sedentary Adults with Arthritis: Effects of a Randomized Controlled Pragmatic Trial

Abstract: Objective To evaluate the impact of Integral-based hatha yoga in sedentary people with arthritis. Methods 75 sedentary adults aged 18+ with rheumatoid arthritis (RA) or knee osteoarthritis (OA) were randomly assigned to 8 weeks of yoga (2 60 min classes and 1 home practice/wk) or waitlist. Poses were modified for individual needs. The primary endpoint was physical health (SF36 Physical Component Summary [PCS]) adjusted for baseline; exploratory adjusted outcomes included fitness, mood, stress, self-efficacy,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 43 publications
1
85
0
1
Order By: Relevance
“…The yoga intervention consisted of 60-minute classes held twice a week for 8 weeks and one weekly home practice [52]. Therefore, yoga exercises may be an adequate form of physical activity for sedentary adults with arthritis.…”
Section: Resultsmentioning
confidence: 99%
“…The yoga intervention consisted of 60-minute classes held twice a week for 8 weeks and one weekly home practice [52]. Therefore, yoga exercises may be an adequate form of physical activity for sedentary adults with arthritis.…”
Section: Resultsmentioning
confidence: 99%
“…Artritli bireylerde sekiz hafta boyunca haftada iki kez 60 dakika uygulanan yoganın, fiziksel aktiviteyi arttırarak hareketliliği artırmaya yardımcı olduğu, fiziksel ve psikolojik sağlık ve sağlıkla ilgili yaşam kalitesini geliştirdiği bildirilmiştir [32]. Yapılan çalışmalarda, diz OA'da konvansiyonel tedavi ile birlikte uygulanan yoganın ağrıyı azalttığı, sürekli kaygı durumu üzerinde etkili olduğu, fonksiyonel düzeyi arttırdığı, günlük aktiviteler, spor, boş zaman faaliyetleri ve yaşam kalitesini yükselttiği belirtilmiştir [33][34][35][36].…”
Section: Yogaunclassified
“…Physical activities shown to improve functioning in older adults include weight training, power training, walking to promote endurance, and yoga [11,15]. In 2015, a study completed at John Hopkins reported that eight weeks of yoga classes improved the physical and mental well-being of people with two common forms of arthritis, knee osteoarthritis and rheumatoid arthritis [16].…”
Section: Older Adults and Physical Activitymentioning
confidence: 99%
“…A well-known benefit of yoga is its ability to reduce stress with the combination of deep breathing and gentle movement [10,24]. There is promising evidence supporting the use of yoga for both pain relief and alleviating the symptoms of arthritis [16].…”
Section: Yoga For Pain Controlmentioning
confidence: 99%